2017 Winter Simulation Conference (WSC) 2017
DOI: 10.1109/wsc.2017.8248000
|View full text |Cite
|
Sign up to set email alerts
|

Using simulation to help hospitals reduce emergency department waiting times: Examples and impact

Abstract: In recent years, all acute hospitals in the UK have experienced unprecedented emergency department waiting times and hospital bed pressures. The consequences are overcrowded emergency departments, ambulance shortages, cancelled elective operations, low staff morale and financial penalties. To deal with the increasing numbers of patient admissions and delayed discharges hospitals must turn now to modelling and simulation to help increase their flexibility and ability to deal with demand variation. Hospitals fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The resulting methodology was able to provide realistic predictions for the system behaviour under different scenarios. Another example of using simulation modeling for reducing waiting times in healthcare was addressed by Monks and Meskarian (2017). The authors concluded that reducing waiting times when emergency departments (EDs) are of low performance is hard to get.…”
Section: Facility Location Decisions In Healtcarementioning
confidence: 99%
“…The resulting methodology was able to provide realistic predictions for the system behaviour under different scenarios. Another example of using simulation modeling for reducing waiting times in healthcare was addressed by Monks and Meskarian (2017). The authors concluded that reducing waiting times when emergency departments (EDs) are of low performance is hard to get.…”
Section: Facility Location Decisions In Healtcarementioning
confidence: 99%
“…By employing the simulation model developed by Perez et al [22], clinics have the opportunity to develop protocols that can minimize waiting times for patients by scheduling doctors and medical assistants according to demand fluctuations. To address issues such as overcrowded emergency departments, Monks and Meskarian [23] used simulation modeling because of its flexibility and ability to handle varying demands in a complex system to solve the problem of overcrowded emergency departments, ambulance shortages, canceled elective surgeries, low staff morale, and financial penalties faced by acute hospitals in the UK.…”
Section: Relevant Literaturementioning
confidence: 99%
“…The educational impact of the model was not an original aim of the study. We, therefore, did not have a substantive educational intervention to hand such as that from SimLean (Robinson, Radnor, Burgess, & Worthington, 2012); however, we did have simple queuing models that could be deployed from working in acute hospitals on similar problems (Monks & Meskarian, 2017). It is interesting to note that the queuing education we provided was to explain the results of the (simple) archetype simulation model.…”
Section: Evidence Of Simulation Improving Healthcare Planningmentioning
confidence: 99%
“…Application in multiplesettings can expose the weaknesses in the design of a generic model and the adaptions that are needed (Robinson et al, 2004). The requirement to recode the, possibly complex, generic model reduces the likelihood of opportunistic reuse and testing of a model by new modelling teams substantially (Monks & Meskarian, 2017). Our approach is to make computer implementations of the model findable, accessible and citable.…”
Section: Introductionmentioning
confidence: 99%